Cuttings of a race: the intervention of an aesthetic ideal of Instagram in the aging of the 21st century (PerCursos, 2023)
Thinking about the multidimensionality of aging as a phenomenon becomes fundamental when taking into account that, beyond all times, humanity always wants to have more time, and for that, it needs to age. And, precisely with this passage of time, the aging process, which is intrinsic to contextual experiences and lifestyles, is modified in its facets and situations, taking into account the way people come to experience their own old age. From this chain of ideas and within a perspective that relates aesthetics and its notions of beauty, and the Internet and its consequences, with “getting old”, this proposal carries out a socio-anthropological reflection on the ways in which Instagram presents the processes facial interventions and, through representations of a recreated ideal, affects the look at the aging process in the 20th century. XXI.
Keywords: aging; onternet; aesthetics; beauty; Instagram